2006
DOI: 10.1177/019027250606900403
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Sentiments and Self-Meanings: Exploring the Modified Labeling Theory of Mental Illness

Abstract: We introduce “stigma sentiments” as a way to operationalize the cultural conceptions of the mentally ill. Stigma sentiments are the evaluation, potency, and activity (EPA) associated with the cultural category “a mentally ill person.” We find consistent support for the validity of the evaluation and potency components as measures of these conceptions. We also demonstrate the validity of EPA ratings of self-identities (“myself as I really am”) and reflected appraisals (“myself as others see me”) as measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 28 publications
6
72
0
1
Order By: Relevance
“…These contexts include physical (Fife and Wright, 2000) and mental illness (Kroska and Harkness 2006;Markowitz 1998), sexual orientation (Hereck et al, 2009), and criminality (Rasmusen1996; Schnittker and John 2007). Corrigan et al (2010) identified two types of stigma: social and self-stigma.…”
Section: Background Literaturementioning
confidence: 99%
“…These contexts include physical (Fife and Wright, 2000) and mental illness (Kroska and Harkness 2006;Markowitz 1998), sexual orientation (Hereck et al, 2009), and criminality (Rasmusen1996; Schnittker and John 2007). Corrigan et al (2010) identified two types of stigma: social and self-stigma.…”
Section: Background Literaturementioning
confidence: 99%
“…Exten sive literature in sociology, psychology, and psy chiatry identifies historical social stigmas and how subgroups overcame them, in some cases in the form of social movements. Members of society have suf fered social discrimination for a broad variety of reasons, including mental illnesses and disorders (Hinshaw, 2007;Kroska and Harkness, 2006), race (Loury, 2003), religion (Khazzoom, 2003), sexual preferences (Gentry, 1987), physical disabilities (Friedman, 2004), or specific behaviors (Stuber et al, 2008), to cite only a few. Gradually the per sons affected by different stigmas and their families form groups to combat, both individually and so cially, their societal rejection.…”
Section: Overcoming the Stigma With Others' Moral Imaginationmentioning
confidence: 99%
“…Although the first and third MLT processes have been investigated in recent studies (Kroska and Harkness, 2006Markowitz, 1998;Markowitz et al, 2011;Rosenfield, 1997;Wright et al, 2000), the second step-the increase in negative evaluation and rejection-has received little attention in recent years, particularly with studies that use a behavioral measure of rejection. Our study begins to address this gap by offering a contemporary examination of the causal link between psychiatric labels and negative evaluation and rejection.…”
Section: Introductionmentioning
confidence: 99%